Analysis of image understanding using clustering under the approach of ant Colony - Ruiz Rivera, María Elena (2013)
The following research paper presents a solution to the problem of high cost of digital storage of images used in various fields such as engineering, medicine, education, architecture, management, entertainment, etc. The solution is based on the implementation of a compression method used in image processing is that of clustering, in which the algorithm ant colony is used, in order to reduce the size of the color palette used to represent an image. This will reduce the storage size of the image without affecting the display of the same by the person.